The Effect of Regional Finance in Improving the Quality of Human Resources in West Sumatra - Guspita, Ega; Febrina Harahap, Erni (KnE Social Sciences, 2022)
The Human Development Index (HDI) has a close relationship with a country’s income. The higher the quality of human resources, the higher the state’s income. This research examined the impact of local revenue, general allocation funds, special allocation funds, and profit-sharing funds on the HDI of West Sumatran districts and cities. This was a descriptive and quantitative study. The data used were secondary data from the Ministry of Finance, Central Bureau of Statistics and other institutions from 2010-2019. Panel data regression analysis was used. The results showed that all of the variables had a positive and significant effect, except for profit-sharing funds which had a negative and significant effect on HDI. This indicated that when more funds are spent on improving human resources, the quality of human resources increases, which is in accordance with previous research. Keywords: HDI, regional finance, districts